Macroprudential policies and private domestic investment in developing countries: An instrumental variables approach - Bao-We-Wal Bambe (German Institute of Development and Sustainability (IDOS), 2025)
This paper examines the effect of macroprudential policies on private domestic investment using a panel of 87 developing countries from 2000 to 2017. Our instrumental variables strategy exploits the geographic diffusion of macroprudential policies across countries, with the idea that reforms in neighbouring countries can affect the adoption or strengthening of domestic reforms through peer pressure or imitation effects. The findings indicate that the tightening of macro-prudential policies significantly reduces private domestic investment. This effect holds for both instruments targeting borrowers and those targeting financial institutions, and is subject to heterogeneity depending on several economic and institutional factors. The transmission channel analysis highlights that the negative impact of macroprudential policies on investment is primarily driven by a reduction in credit supply and financial inclusion.
Keywords: E22; E44; G28; 320; Macroprudential policies; private domestic investment; developing countries; instrumental variables